2014
DOI: 10.1007/s11207-014-0548-0
|View full text |Cite
|
Sign up to set email alerts
|

Determining the 3D Structure of the Corona Using Vertical Height Constraints on Observed Active Region Loops

Abstract: The corona associated with an active region is structured by hightemperature, magnetically-dominated closed and open loops. The projected 2D geometry of these loops is captured in EUV filtergrams. In this study using SDO/AIA 171Å filtergrams, we expand our previous method to derive the 3D structure of these loops, independent of heliostereoscopy. We employ an automated loop recognition scheme (Occult-2) and fit the extracted loops with 2D cubic Bézier splines. Utilizing SDO HMI magnetograms, we extrapolate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Here we briefly review the procedures of tracing and fitting the coronal loops developed by Gary et al (2014b). First, an automated loop recognition scheme (the code OCCULT-2) is employed to trace the loop structures from the EUV images taken by SDO/AIA in 171 Å.…”
Section: Coronal Loop Tracing and Fittingmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we briefly review the procedures of tracing and fitting the coronal loops developed by Gary et al (2014b). First, an automated loop recognition scheme (the code OCCULT-2) is employed to trace the loop structures from the EUV images taken by SDO/AIA in 171 Å.…”
Section: Coronal Loop Tracing and Fittingmentioning
confidence: 99%
“…Recently, Gary et al (2014b) developed a new method of deriving the 3D structure of observed 2D coronal loops independent of heliostereoscopy, and suggested that it can determine the matching of extrapolated magnetic fields with coro-nal loops. In that method, an automated loop recognition scheme (OCCULT-2, Aschwanden et al 2013) is first used to extract 2D loop structures from EUV images and then the extracted loops are fitted with 2D cubic Bézier splines that are based on 4 control points (Gary et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It occurred near disk center at position N14W18. Because of its intensity and its location, the flare has been the object of many studies (Petrie 2012;Wang et al 2012;Feng et al 2013;Jiang et al , 2014aZharkov et al 2013;Gary et al 2014;Liu et al 2014;Yang et al 2014;Xu et al 2014). The flare, as recorded by the Geostationary Orbiting Environmental Satellites (GOES), started at 22:12 UT, peaking around 22:20 UT.…”
Section: The X-class Flare Event Of 6 September 2011mentioning
confidence: 99%